Consistent increase in herbivory along two experimental plant diversity gradients over multiple years. Issue 7 (18th July 2017) - Meyer, Sebastian T.; Scheithe, Lukas; Hertzog, Lionel; Ebeling, Anne; Wagg, Cameron; Roscher, Christiane; Weisser, Wolfgang W.
Abstract: Research on the functional importance of biodiversity, motivated by global species loss, has documented that plant species richness affects many plant‐related ecosystem functions. Less is known about the effects of plant species richness on functions related to higher trophic levels, such as the consumption of biomass by animals, that is, herbivory. Previous studies have shown positive, neutral, or negative effects of plant species richness on herbivory. In the framework of a grassland biodiversity experiment (the Jena Experiment), we investigated herbivory (the proportion of leaf area damaged and the amount of leaf biomass consumed by arthropod herbivores) along two experimental gradients of plant species richness ranging from 1 to 60 species (Main Experiment) and from 1 to 8 species (Trait‐Based Experiment) biannually for five and three years, respectively. Additionally, plant functional diversity, based on traits related to plant growth, was manipulated as the number of functional groups in a community (Main Experiment) or a gradient of functional trait dissimilarity (Trait‐Based Experiment). Herbivory at the level of plant communities ranged from 0% to 31% (0 and 33.8 g/m 2 ) in the Main Experiment and 0% to 8% (0 and 13.7 g/m 2 ) in the Trait‐Based Experiment, and it was on average higher in summer than in spring. For both experimental gradients and all years investigated, we found a consistent increase in damaged leaf area and consumed biomass with increasing plant species richness. As mechanistic explanations for effects of plant species richness, we propose changes in plant quality and herbivore communities. The presence of specific plant functional groups significantly affected herbivory, likely related to traits affecting plant defense and nutritional value, but we found little evidence for effects of plant functional diversity. The general positive relationship between plant species richness and herbivory might contribute to effects of plant species richness on other ecosystem functions such as productivity and nutrient mineralization and can cascade up the food web also affecting higher trophic levels.